Full elucidation of the transmembrane anion transport mechanism of squaramides using in silico investigations. Issue 32 (6th July 2018) - Marques, Igor; Costa, Pedro M. R.; Q. Miranda, Margarida; Busschaert, Nathalie; Howe, Ethan N. W.; Clarke, Harriet J.; Haynes, Cally J. E.; Kirby, Isabelle L.; Rodilla, Ananda M.; Pérez-Tomás, Ricardo; Gale, Philip A.; Félix, Vítor
Abstract : The anion carrier mechanism promoted by squaramide-based molecules has been elucidated by molecular dynamics and chloride efflux studies. Abstract : A comprehensive experimental and theoretical investigation of the transmembrane chloride transport promoted by four series of squaramide derivatives, with different degrees of fluorination, number of convergent N–H binding units and conformational shapes, is reported. The experimental chloride binding and transport abilities of these small synthetic molecules in liposomes were rationalised with quantum descriptors and molecular dynamics simulations in POPC bilayers. The tripodal tren-based compounds, with three squaramide binding motifs, have high chloride affinity, isolating the anion from water molecules within the membrane model and preventing its release to the aqueous phase, in agreement with the absence of experimental transport activity. In contrast, the symmetrical mono-squaramides, with moderate chloride binding affinity, are able to bind and release chloride either in the aqueous phase or at the membrane interface level, in line with experimentally observed high transport activity. The PMF profiles associated with the diffusion of these free transporters and their chloride complexes across phospholipid bilayers show that the assisted chloride translocation is thermodynamically favoured.